Free growth of one-dimensional β-Ga2O3 nanostructures including nanowires, nanobelts and nanosheets using a thermal evaporation method. Issue 12 (September 2016) - Abdullah, Q.N.; Yam, F.K.; Mohmood, K.H.; Hassan, Z.; Qaeed, M.A.; Bououdina, M.; Almessiere, M.A.; Al-Otaibi, A.L.; Abdulateef, S.A.
Abstract: Large-scale β-Ga2 O3 nanostructures (nanowires-NWs, nanobelts-NBs and nanosheets-NSs) were synthesized via thermal evaporation of GaN powder in an ambient argon atmosphere. The effect of the substrate type (Si, AlN-thin film/Si and ZnO-thin film/Si) on the growth of β-Ga2 O3 nanostructures was investigated. The morphology changes from NWs to NBs or NSs when the substrate changes from Si to AlN-thin film/Si or ZnO-thin film/Si, respectively. The size and dimensionality were the most influential parameters on the structure of the as-grown β-Ga2 O3 . The as-grown nanostructures crystallize within the monoclinic crystal structure of the β-Ga2 O3 phase. The obtained nanostructures show intense blue-red emission characterized by a broadband photoluminescence spectrum with peaks located at 430, 500–525 and 688–700 nm. These emissions originate from the defect-related donor-acceptor pair recombination mechanism and depend on the nanostructure dimensionality and morphology. A vapor-solid growth mechanism for the growth of various β-Ga2 O3 nanostructures was also proposed.